1999
DOI: 10.1073/pnas.96.5.2485
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of N -methyl- d -aspartate receptor activation suppresses learning-induced synaptic elimination

Abstract: Auditory filial imprinting in the domestic chicken is accompanied by a dramatic loss of spine synapses in two higher associative forebrain areas, the mediorostral neostriatum͞hyperstriatum ventrale (MNH) and the dorsocaudal neostriatum (Ndc). The cellular mechanisms that underlie this learning-induced synaptic reorganization are unclear. We found that local pharmacological blockade of N-methyl-D-aspartate (NMDA) receptors in the MNH, a manipulation that has been shown previously to impair auditory imprinting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…The presence of glutamate receptor subunits in this brain area is in agreement with the large amount of literature that demonstrates the crucial role played by glutamate in the long-term potentiation (LTP), a process that was discovered and takes place in a prominent manner in the hippocampus (Morris et al, 1986;Steele et al, 1995;Bock and Braun, 1999). LTP is a long-lasting synaptic enhancement caused by the repeated activation of excitatory synapses.…”
Section: Functional Implicationssupporting
confidence: 58%
“…The presence of glutamate receptor subunits in this brain area is in agreement with the large amount of literature that demonstrates the crucial role played by glutamate in the long-term potentiation (LTP), a process that was discovered and takes place in a prominent manner in the hippocampus (Morris et al, 1986;Steele et al, 1995;Bock and Braun, 1999). LTP is a long-lasting synaptic enhancement caused by the repeated activation of excitatory synapses.…”
Section: Functional Implicationssupporting
confidence: 58%
“…These experiments demonstrated that the activation of NMDA receptors is required for auditory filial imprinting (Bock et al, 1996), for the induction of long-term potentiation-like potentiation (Wang et al, 1994), and for the learninginduced synaptic reorganization (Bock and Braun, 1999). Our results presented here indicate that the activation of this receptor, which normally occurs via activation of glutamatergic afferents from the dorsomedial thalamus (Metzger et al, 1996b), may induce a suppression of the dopaminergic system arising from ventral tegmental afferents (Metzger et al, 1996b), and of the serotonergic system from nuclei raphe afferents (Metzger et al, 1996a).…”
Section: Implications For Learningmentioning
confidence: 97%
“…During early postnatal life, apoptosis (Simonati, Rosso, & Rizzuto, 1997;Williams & Rakic, 1988) and pruning of both redundant neuronal processes and non-functional dendritic synapses (Herschkowitz, 1988;Huttenlocher, 1979;Huttenlocher, De Courten, Garey, & van der Loos, 1982;Purves & Lichtman, 1980) are probably the most significant determinants of regional volumes. By eliminating redundant neuronal processes, dendritic branches, and supernumerary synaptic spines, pruning supports learning and development of psychomotor skills (Bock & Braun, 1998;Bock & Braun, 1999;Nixdorf-Bergweiler, Wallhausser-Franke, & DeVoogd, 1995;Rakic, Bourgeois, & Goldman-Rakic, 1994;Rausch & Scheich, 1982;Rollenhagen & Bischof, 1994;Wallhausser & Scheich, 1987). Moreover, human postmortem studies of the cerebral cortex have demonstrated a 40-50% decrease in synaptic density in frontal and parietal cortices between infancy and late adolescence (Huttenlocher, 1979;Huttenlocher, 1984;Huttenlocher & de Courten, 1987).…”
Section: Possible Ultrastructural Determinantsmentioning
confidence: 99%